Developing an impact-focused typology of socially responsible fund providers - Joel Diener; André Habisch (Journal of Risk and Financial Management, 2022)
The concept of investor impact of socially responsible investments is relatively new. Our article expands knowledge in this field by analyzing how investor impact is implemented in the ethical investment policies of 45 providers of publicly traded, socially responsible funds. Based on a typological content analysis, we first develop an impact-focused category system, which in the second step is used to distinguish three types of fund providers: ESG hermits, ESG ambassadors and ESG evangelists. Our results suggest that socially responsible fund providers with a stronger impact orientation, such as ESG evangelists, also employ strategies that are more likely to achieve investor impact. In contrast, fund providers with a weaker impact orientation, such as ESG hermits, focus more on purity aspects and therefore tend to utilize strategies that defend the purity claim but also show a weaker investor impact.
Keywords: 650; investor impact; shareholder engagement; socially responsible investments; SRI; sustainable development goals; sustainable investing; typological content analysis